2019
DOI: 10.1111/ijun.12182
|View full text |Cite
|
Sign up to set email alerts
|

A literature review about self‐care on ostomy patients and their caregivers

Abstract: Self‐care is a key concept for ostomy patients as much as for chronically ill patients. Many studies describe how reaching a good self‐care level permits patient to perceive a higher quality of life, to adjust faster to the new condition, to grow empowerment feelings and to reduce readmissions and negative outcomes. There are many studies that state the negative impact of living with an ostomy on patients' quality of life. Quality of life is proven to be strictly related to self‐care ability. Health profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 31 publications
(117 reference statements)
1
37
0
3
Order By: Relevance
“…Ostomy type was a predictor of adjustment as well: people with urostomy showed not only lower levels of acceptance, but also lower negative feelings. A urostomy is often permanent, and it is rarely used outside of oncology; consequently, patients with a urostomy may have been influenced by these two aspects 7,16,27 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ostomy type was a predictor of adjustment as well: people with urostomy showed not only lower levels of acceptance, but also lower negative feelings. A urostomy is often permanent, and it is rarely used outside of oncology; consequently, patients with a urostomy may have been influenced by these two aspects 7,16,27 …”
Section: Discussionmentioning
confidence: 99%
“…A urostomy is often permanent, and it is rarely used outside of oncology; consequently, patients with a urostomy may have been influenced by these two aspects. 7,16,27…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with a permanent ostomy can live with it even for several years (Krouse et al., 2016) if we consider the ostomies as the result of colorectal (Sun et al., 2013) or bladder cancer (Jensen, Kiesbye, Soendergaard, Jensen, & Kristensen, 2017), which have a 5‐year survival rate of between 40% and 65% (Liu et al., 2016; Siegel et al, 2017). Therefore, an ostomy can lead to complex and lifelong consequences for patients (Villa, Mannarini, et al, 2019; Wen et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Studies of several pre-and postoperative follow-up programs and education in ostomy care performed by stoma care nurses (SCNs) have shown that such follow-up and education promote the patient's self-care and adjustment process to life with an ostomy. 4,[9][10][11] Questionnaires such as The Ostomy Adjustment Inventory 23, 12 the Stoma Selfefficacy scale [13][14][15] and the Ostomy Adjustment Scale (OAS) [16][17][18][19][20] has been validated in several countries and used to measure psychosocial adjustment to ostomy.…”
Section: Introductionmentioning
confidence: 99%